THE ESTIMATION OF A PSYCHOPHYSIOLOGICAL AIRCRAFT PILOT WORKLOAD IN SITUATIONS AFFECTING THE FLIGHT SAFETY - P. M. Polyakov; M. V. Karmyzov; S. V. Monakhova (Научный вестник МГТУ ГА, 2016)
The article proposes the use of various medical methods to assess human psychophysiological state in the event of special situations in flight. Such an approach would set clearer boundaries of psycho-physiological stress on night personnel in flight for flight safety providing.